Pharmacological investigation of brucine anti-ulcer potential - Noman, Muhammad; Qazi, Neelum Gul; Rehman, Najeeb Ur; Khan, Arif-ullah (Frontiers in Pharmacology, 2022)
Gastric ulcer is one of the most common chronic gastrointestinal disease characterized by a significant defect in the mucosal barrier. The current study has been conducted to evaluate brucine anti-ulcer effect. Brucine has binding energy values of - 2.99 to - 8.11 Kcal/mol against chosen targets, according to in-silico research. Brucine exhibits inhibitory effect against helicobactor pylori. In-vivo findings revealed that brucine (3 mg/Kg) showed effective result in healing ethanol-induced ulcer lesions of gastric region in rats. Brucine shown inhibitory effect against H+/K+-ATPase. Levels of glutathione, glutathione-s-transferase and catalase enhanced in the gastric rat tissue with the use of brucine while significant decrease in lipid peroxide level was seen. Histopathological evaluation showed improvement in cellular architecture and decrease in inflammatory indicators like cyclooxygenase, tumour necrosis factor, and nuclear factor kappa B expression, validated through immunohistochemistry, enzyme-linked immunosorbent assay and western blot techniques. In the reverse transcription-polymerase chain reaction brucine decreased H+/K+-ATPase mRNA levels. This study reveals that brucine possess stable binding affinities against selected targets. Brucine exhibits anti-ulcer effect, mediated via anti-H. pylori, H+/K+-ATPase inhibition, anti-oxidant and anti-inflammatory pathways.